Suicidality in obsessive compulsive disorder (OCD): A systematic review and meta-analysis. (July 2015) - Angelakis, Ioannis; Gooding, Patricia; Tarrier, Nichoas; Panagioti, Maria
Abstract: Although a growing number of studies have examined the frequency of suicidal thoughts and behaviors in individuals with obsessive compulsive disorder (OCD), there is controversy about the frequency and burden of suicidality in OCD. This is the first systematic review aimed at examining the association between suicidality and OCD and at providing evidence about psychological mechanisms that may underlie suicidality in those with OCD. Five electronic bibliographic databases were searched up to April 2014: Medline, PsycINFO, Embase, Web of Science and CINAHL. Meta-analysis using random effects models was conducted. Forty-eight studies were included in the systematic review. The pooled effect size across 30 independent comparisons revealed a moderate to high, significant association between suicidality and OCD (Hedges' g = 0.66, 95% confidence interval 0.49–0.82) which persisted across different types of suicidality including suicidal ideation and suicide attempts. Comorbid Axis I disorders, increased severity of comorbid depressive and anxiety symptoms, increased severity of obsessions, feelings of hopelessness and past history of suicide attempts were associated with worsening levels of suicidality in OCD. There was no indication for publication bias but the methodological quality of the studies was low. The theoretical, research and clinical implications of these findings are emphasized. Highlights: The link between a diagnosis of OCD and suicidality was examined. A high, significant association between OCD and suicidality was established. Comorbid depression worsened the severity of suicidality in OCD. The methodological quality of the studies included in the review was low. Theory-driven studies are needed to examine the mechanisms of suicidality in OCD.